Transport Stress Changes Blood Biochemistry, Antioxidant Defense System, and Hepatic HSPs mRNA Expressions of Channel Catfish Ictalurus punctatus - Refaey, Mohamed M.; Li, Dapeng (Frontiers in Physiology, 2018)
Transport procedures usually cause fish stress. The purpose of this study was to investigate the effect of transport stress on blood biochemical profiles, oxidative stress biomarkers, and hepatic heat shock proteins (HSPs) of channel catfish (Ictalurus punctatus). Fish (body weight 55.57± 5.13 g) were randomly distributed to two groups, the control and the treatment. The control group was kept under the normal culture conditions. The treatment group was exposed to the process of transport (3.5 hrs.). Fish samples were collected before transport, after packing and at 0, 1, 6, 24, 72, and 168 h after transport, respectively. Transport caused a significant increase in the serum concentrations of cortisol, glucose, total cholesterol, and triglyceride, as well as the activity of aspartate aminotransferase at 0 h and 1 h after transport compared with non-transported fish and the basal level. Blood total protein content significantly declined in the transported fish. Total antioxidant capacity, malonaldehyde content, and the activities of both glutathione peroxidase and catalase significantly increased in fish within 6 hours after transport. The transported fish exhibited a significant higher level in either the concentration of nitric oxide or the mRNA expressions of both hepatic HSP70 and HSP90. It is concluded that transport triggers stress response of I. punctatus, leading to the obvious change in antioxidant capacity. I. punctatus need to be more care after transport to recover from transport stress.